Pengaruh Kepercayaan dan Nilai Dirasakan Terhadap Loyalitas Pelanggan pada Pempek Selendang Mayang - Maharani, Delisti; Kasih, Yulizar (Universitas Multi Data Palembang, 2025)
This study aims to analyze the influence of trust and perceived value on customer loyalty to Pempek Selendang Mayang, both partially and simultaneously. Using a descriptive quantitative method with a Likert scale questionnaire, the study involved 161 respondents selected using the Slovin method and analyzed with SPSS. The results indicate that trust and perceived value have a positive and significant effect on customer loyalty to Pempek Selendang Mayang.